Upaya Cegah Tangkal (Cekal) Pelaku Tindak Pidana Korupsi Melalui Peran Intelijen Kejaksaan - Falielian, Fransiska Fitry; Amrullah, Rinaldy; Tamza, Fristia Berdian; Achmad, Deni; Susanti, Emilia (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The roIe of the Prosecutor's Office lnteIIigence in conducting preventive measures against perpetrators of corruption is cruciaI in efforts to eradicate corruption in lndonesia. This study aims to analyze the methods and effectiveness of the Prosecutor's Office inteIIigence actions in preventing the ban of perpetrators of corruption, with a focus on the Lampung High Prosecutor's Office. This research uses normative and empiricaI juridicaI approaches, and data is collected using qualitative analysis.